Morphology of Root Canals in Mandibular Third Molar in Pakistani Population - Ahmed, Muhammad Rauf (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine the number and morphology of root canals in mandibular third molar teeth in Pakistani population. METHODS: This prospective cross-sectional study was conducted in department of dentistry, Faisalabad Medical University Faisalabad. Sixty(60) patients with irreversible pulpitis in erupted mandibular third molars having age 25-60 years were selected. A total of seventy (70) teeth were evaluated from 1-Jan-2017 to 31-Aug-2017. Periapical x-rays were done in every patient to analyze the umber and morphology of root canals. Root canals (RC) were prepared and filling was done using cold lateral compaction technique and restoration was done. After restoration, again x-rays was taken to confirm any missing root canal. RESULTS: The mean age of study patients was 43.2 +6.3 years. There were 37 (61.7%) males and 23 (38.3%) female patients. Regarding number of root canals, 3 root canals were diagnosed in 43 (61.43%) teeth, 4 root canals in 16 (22.86%) teeth and 2 root canals in 8 (11.43%) teeth. Regarding classification of root canals types, type I root canals in 37 (52.86%) teeth, type II in 13 (18.57%) teeth, and type III in 8 (11.43%) teeth. CONCLUSION: Present study results showed that 3 and 4 root canals are most common in our population.